The Reliability and Criterion Validity of the Diagnostic Infant and Preschool Assessment: A New Diagnostic Instrument for Young Children - Scheeringa, Michael S. (2010)
The need to assess Diagnostic and Statistical Manual, Fourth Edition (DSM-IV) disorders in children younger than 7 years of age has intensified as clinical efforts to diagnose and treat this population have increased, and clinical research on psychopathology has advanced. A new diagnostic instrument for young children was created, the Diagnostic Infant Preschool Assessment (DIPA), and was tested for test–retest reliability and concurrent criterion validity. The caregivers of 50 outpatients aged 1–6 years were interviewed twice by trained interviewers, once by a clinician and once by a research assistant, about eight disorders. The median test–retest intraclass correlation was 0.69, mean 0.61, and values ranged from 0.24 to 0.87. The median test–retest kappa was 0.53, mean 0.52, and values ranged from 0.38 to 0.66. There were no differences by duration between interviews. Concurrent criterion validity show good agreement between the instrument and DSM-based Child Behavior Checklist scales when the DSM-based scales were matched well to the disorder (attention-deficit/hyperactivity inattentive and hyperactive and oppositional disorders). Preliminary data support the DIPA as a reliable and valid measure of symptoms in research and clinical work with very young children. This measure adds a tool that is flexible in covering both DSM-IV syndromes and empirically-validated developmental modifications that can help increase confidence in assessing young children, ensuring coverage of symptoms, and improve access to care.